IL-17 mediated inflammation promotes tumor growth and progression in the skin. - Donggou He; Hui Li; Nabiha Yusuf; Craig A Elmets; Mohammad Athar; Santosh K Katiyar; Hui Xu (PLoS ONE, 2012)
The mechanism for inflammation associated tumor development is a central issue for tumor biology and immunology and remains to be fully elucidated. Although IL-17 is implicated in association with inflammation mediated carcinogenesis, mechanisms are largely elusive. In the current studies, we showed that IL-17 receptor-A gene deficient (IL-17R-/-) mice were resistant to chemical carcinogen-induced cutaneous carcinogenesis, a well-established inflammation associated tumor model in the skin. The deficiency in IL-17R increased the infiltration of CD8+ T cells whereas it inhibited the infiltration of CD11b+ myeloid cells and development of myeloid derived suppressor cells. Inflammation induced skin hyperplasia and production of pro-tumor inflammatory molecules were inhibited in IL-17R-/- mice. We found that pre-existing inflammation in the skin increased the susceptibility to tumor growth, which was associated with increased development of tumor specific IL-17 producing T cells. This inflammation induced susceptibility to tumor growth was abrogated in IL-17R-/- mice. Finally, neutralizing IL-17 in mice that had already developed chemical carcinogen induced skin tumors could inhibit inflammation mediated tumor progression at late stages. These results demonstrate that IL-17 mediated inflammation is an important mechanism for inflammation mediated promotion of tumor development. The study has major implications for targeting IL-17 in prevention and treatment of tumors.